Comparison of the effects of variables in sperm preparation techniques on pregnancy rates in intrauterine insemination - Kocaman, Nevin (My University, 2019)
Aim: To investigate the effects of two sperm preparation techniques, density gradient centrifugation (DGC) and swim-up, on thepregnancy rates per cycle and per group in two intrauterine (IUI) cycles.Material and Methods: The retrospective study reviewed 634 patients who presented to Firat University Medical School Hospital andunderwent a total of 1,032 IUI cycles. Group I consisted of 306 (48.3%) patients who underwent a total of 524 IUI cycles betweenJanuary 2012 and January 2016 and Group II included 328 (51.7%) patients who underwent a total of 508 IUI cycles between April 2015and January 2019. The study investigated the effects of technical changes applied to sperm preparation techniques on pregnancyrates in both groups.Results:A significant difference was found between the clinical pregnancy rates of the two groups with regard to the numbers ofpatients and IUI cycles (p<0.001). The technique used in Group II increased the pregnancy rate by 3.195 times compared to thetechnique used in Group I. A logistic regression analysis revealed that the pregnancy rate in the first cycle was 3.530 times higher thanthat of the second cycle in both groups.Conclusion: The results indicated that the application of suitable alterations in sperm preparation techniques by taking into accountthe potential effect of all factors is likely to affect clinical pregnancy rates in IUI.
Keywords: Kadın Hastalıkları ve Doğum